THE EFFECTS OF CONTROLLED SKIDDING TECHNIQUE ON RESIDUAL STAND DAMAGE AND GROUND EXPOSURE IN SWAMP FOREST LOGGING - Sona Suhartana (Indonesian Journal of Forestry Research, 2004)
The  case study was  carried  out at a swamp forest company  in Riau in 2001.   The  aim of the study  was to determine  the effect of controlled skidding technique  to residual  stand damage and ground  exposure. Data  collected  includes:  felled trees, poles,   trees with  the diameter 20 cm up, damaged poles, damaged  trees and ground  exposure.  The data was  analyzed with t-test.  The study showed  the following results:The  average of  residual stand  damage caused by controlled  skidding technique  was  29.05% for poles and 19.8%  for trees. The average of residual stand damage caused by conventional skidding technique  was 34.2% for poles and  24.9%   for trees.  The difference  of  5.1%   (poles) and 5.1 % (trees) were significant  at 95%.The  average of ground  exposure  caused by controlled  skidding  technique  and conventionalskidding technique was respectively   16.06% and 18.4%.  The difference of 2.34%  was significant at 95%.